Critérios para utilização de implantes protéticos com o apoio da Sociedade Brasileira de Quadril: um guia prático - Greiffo, Rosane Helena (2012)
Identification factors related to safety and quality of prostheses for total hip arthroplasty according to the orthopedic specialists, as well as the search and checking for information from the legal instruments of regulation such as the registry made by the Ministry of Health and corresponding label functioning instructions containing the exact description of the characteristics of the devices, alert notifications for technical surveillance, etc., can lead to criteria that minimize errors and avoid adverse events when choosing hip implants, during the process of request, release, deliver and use of the product. In order to investigate this context, a survey was made by means of a questionnaire where members of the Hip Brazilian Society answered selected questions. Data from answers have shown that 72% of respondents do not believe that the ANVISA (National Health Agency) product registration is part of a safety and quality process for health products in Brazil, and another 72% are unaware of the pos market monitoring tool called Tecnovigilância. However, 94% of the medical doctors state that they already have found prosthetic failure throughout their career, other 94% indicate that the failure occurred with national prostheses, and in 60% of these cases the supplier was contacted and not the ANVISA, and for other 30 % of failures nothing was done. The exposure of these data is worrying since it reflects the gap between ANVISA and the physicians in regard to monitoring health technologies. Also, the doctors do not notify adverse events to the regulatory Agency and the Agency therefore does not disseminate this tool to those who actually should be the focus of attention since they use the products in their daily practice. Finally, in order to facilitate data verification of health products, in special hip phrostheses, a practical electronic guide was developed where questions and doubts about safety and quality of medical devices can be checked according to the ANVISA procedures.